2003
DOI: 10.1111/j.1365-2621.2003.tb09641.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Limitation of Acrylamide Formation in Fried and Baked Corn Chips and in French Fries

Abstract: The effects of lowering pH by an acidulant (citric acid) on the formation of acrylamide in fried and baked corn chips and in french fries were studied by using a GC/MS. The 0.2% citric acid treatments induced 82.2% and 72.8% inhibition of acrylamide formation in fried and baked corn chips, respectively. Dipping potato cuts in 1% and 2% citric acid solutions for 1 h before frying showed 73.1% and 79.7% inhibition of acrylamide formation in french fries. In the experiment of heating 1 mL solution containing aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
162
4
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(199 citation statements)
references
References 4 publications
25
162
4
3
Order By: Relevance
“…Climate, in particular temperature, has a strong influence on sugar metabolism in potatoes: reducing sugars can vary by more than a factor of four for a given cultivar between different harvests [24]. High temperature (29 C) decreased tuber growth [29] and led to a stronger incorporation of 14 C into sucrose and less incorporation into starch [30]. The callus tissue of cultivar Russet Burbank was shown to contain more reducing sugars after eight weeks at 30 C compared to 20 C [31].…”
Section: Comparison Of the 2002 And 2003 Harvestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate, in particular temperature, has a strong influence on sugar metabolism in potatoes: reducing sugars can vary by more than a factor of four for a given cultivar between different harvests [24]. High temperature (29 C) decreased tuber growth [29] and led to a stronger incorporation of 14 C into sucrose and less incorporation into starch [30]. The callus tissue of cultivar Russet Burbank was shown to contain more reducing sugars after eight weeks at 30 C compared to 20 C [31].…”
Section: Comparison Of the 2002 And 2003 Harvestsmentioning
confidence: 99%
“…In order to decrease the acrylamide contents of these products, various approaches were employed: the frying process was optimized and strictly controlled [12]; citric acid was added [13,14]; and asparaginase was successfully applied [6]. However, in practice, any technological effort to limit the acrylamide formation in heated potato products is in vain if the raw material is not suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these additives have inhibition effects, such as organic acids [16,17], chlorates [17,18,19], phenolic compounds [20,21], and plant extract [22,23]. In contrast, several of these additives have promoting effects, such as sucrose [24] and butylated hydroxytoluene [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some research [13] aimed at finding conditions that might reduce or prevent the formation of acrylamide in foods, concluded that adding the ground aromatic rosemary to olive oil resulted in a 25% reduction in acrylamide formation in fried potato slices. Acid treatments have also been found to be effective in preventing acrylamide formation since they lower pH into the range where acrylamide formation is minimized (<pH 5) [14]. Thus, by incorporating R. battenbergiana extract in refined bleached deodorized (RBD) palm olein, the quality of the frying oil is expected to be preserved even during repeated frying, thereby extending the frying life of the treated oil.…”
Section: Introductionmentioning
confidence: 99%